Expanding the Family of Monosubstituted 15-Membered Pyridine-Based Macrocyclic Ligands for Mn(II) Complexation in the Context of MRI - Pražáková, Marie; Ndiaye, Daouda; Tóth, Éva; Drahoš, Bohuslav (Inorganic chemistry, 2025)
As Mn(II) complexes attract continuous interest as alternatives to Gd-based contrast agents (CAs) in clinical magnetic resonance imaging (MRI), we synthesized two monosubstituted derivatives of the 15-membered pyridine-based macrocycle 15-pyN3O2 bearing either a 2-pyridylmethyl (L2) or a 2-benzimidazolylmethyl pendant arm (L3) and characterized their Mn(II) complexes MnL2 and MnL3 in the context of MRI contrast agent development. Their X-ray molecular structures confirmed a coordination number of seven and a pentagonal bipyramidal geometry with one coordination site available for inner-sphere water. Protonation constants of L2 and L3, and stability constants with selected divalent metal ions were determined using potentiometry. MnL2 and MnL3 complexes are fully formed at pH 7.4; however, they both display low kinetic inertness due to a significant spontaneous dissociation of the nonprotonated complex. The presence of one inner-sphere water molecule in the Mn(II) complexes was confirmed by 17O NMR and 1H NMRD measurements. The water exchange rate constants are very low (kex298 = 0.46 × 107 and 0.23 × 107 s-1 for MnL2 and MnL3, respectively), but typical for Mn(II) complexes of 15-pyN3O2 derivatives. The relaxivities are in good agreement with monohydrated small-molecular-weight Mn(II) chelates (r1 = 2.49 and 2.77 mM-1 s-1 at 20 MHz, 25 °C, for MnL2 and MnL3, respectively).